" The status of the countries of the Balkan Peninsula in the United States of America strategy after the Cold War " (Tikrit Journal For Political Science, 2022)
The United States of America seeks to secure its global or regional position through control and influence over strategic regions, including the Balkans, which is an important part of the interests of international and regional powers seeking to benefit from the important geostrategic position of the region in drawing up its policies and strategies in the future, in light of the elements of strength and ability that it employs to exercise influence. influence in the region, Which necessitates the Balkan countries to take policies and build internal and external relations in their regional surroundings with the international and regional powers in order to be able to achieve their interests and goals in light of the existing competition, which makes the visions about the future of the region vary between the points of convergence in the interests of the Balkan countries with the policies of the competing powers and the points of intersection with Others, and each of them seeks to achieve or preserve them, all of this pushes the international and regional powers to formulate military, political and economic strategies to build an important future role in order to achieve their goals.
Keywords: • countries of the Balkan Peninsula • United States of America • Strategy • Regional complexities and historical tensions • Objectives of promoting stability and democracy • Role of military cooperation and alliances • Counterterrorism efforts and security enhancement